Giving something back: how reciprocal motivation drives entrepreneurs to contribute to their entrepreneurial ecosystem - Johannes Hähnlein; Matthias Baum; Carolin Durst (Small Business Economics, 2025)
Entrepreneurial ecosystems thrive on the contributions of diverse actors, among whom entrepreneurs play a pivotal role. Interestingly, previous research on entrepreneurial ecosystems has remained silent on how to encourage entrepreneurs to “give back” to their ecosystem. This study probes the phenomenon of downward causation, aiming to unravel the motivations and mechanisms driving entrepreneurs to actively contribute to the evolution and stability of their ecosystems. Drawing on qualitative analyses of 32 in-depth interviews with startup entrepreneurs in Germany, our findings unveil the characteristics of contribution behavior and highlight the heterogeneous nature of entrepreneurs' motivations. Reciprocal motivation emerges as a central driver, influenced by a complex interplay of interactions. Experiences with ecosystem actors shape diverse interpersonal relationships, impacting entrepreneurs' gratitude and fostering a sense of affiliation. Individual characteristics, such as entrepreneurial passion and altruism, along with the situational context, can reinforce or constrain this motivation. These insights converge into a dynamic model, enhancing theoretical foundations of downward causation within entrepreneurial ecosystems.
Keywords: A13; L26; L53; M13; M20; O31; R00; R11; R58; 330; Entrepreneurship; Entrepreneurial ecosystems (EEs); Downward causation; Microfoundations; Evolution